2021
DOI: 10.1049/cmu2.12284
|View full text |Cite
|
Sign up to set email alerts
|

A sequential roadmap to Industry 6.0: Exploring future manufacturing trends

Abstract: It has been speculated that by the year 2050, technology will have progressed to the point of complete autonomy. This paper scrolls through patent pathways and intellectual developments throughout the industrial revolutions listing significant products and services that landmarked each revolution up to Industry 4.0. The patent trails and the recent IPR inputs are expected to assist readers in fast‐tracking up to speed on the bleeding edge of the current research pools while having an eagle's eye perspective on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Industry 5.0 represents some exclusive limitations and responses such as high price responsibilities in manufacturing policies, standardization, and legalization in all policies to preclude any thoughtful problem among the digital technology, society perspective, and business [40]. The probabilities of social heterogeneity among the society in relations of values and adapting the new technologies of a new revolution, measurement of ecological balance and social values, significant investment and integration of all the customers from high business to SMEs, and environment based new policies with agility, outcome-based [41], and greater dependency on technologies [42]. As a noble initiative by business, Finland in ''From industry X to industry 6.0'' was sketched a series of predictive implementation strategies, policies, investment, business landscape, Research and development, and manufacturing ecosystem and future path dimensions to promote industry 6.0 [1].…”
Section: Technologies Descriptions Referencesmentioning
confidence: 99%
“…Industry 5.0 represents some exclusive limitations and responses such as high price responsibilities in manufacturing policies, standardization, and legalization in all policies to preclude any thoughtful problem among the digital technology, society perspective, and business [40]. The probabilities of social heterogeneity among the society in relations of values and adapting the new technologies of a new revolution, measurement of ecological balance and social values, significant investment and integration of all the customers from high business to SMEs, and environment based new policies with agility, outcome-based [41], and greater dependency on technologies [42]. As a noble initiative by business, Finland in ''From industry X to industry 6.0'' was sketched a series of predictive implementation strategies, policies, investment, business landscape, Research and development, and manufacturing ecosystem and future path dimensions to promote industry 6.0 [1].…”
Section: Technologies Descriptions Referencesmentioning
confidence: 99%
“…Due to the lack of technologies owned by the industry, it faces various challenges like production, distribution, supply chain management etc [279]. By the year 2050, technology will have progressed to the level of autonomy [80]. The industries are categorized into three economic sectors: primary, secondary, and tertiary [24].…”
Section: Smart Industrymentioning
confidence: 99%
“…The capability of humans, interaction with computers, and robot workers gives efficient and effective results [279]. This industry proposed the 3D techniques (like 3D printing or additive manufacturing is used for creating 3D objects) with the use of IoT [80].…”
Section: Industry Evolutionmentioning
confidence: 99%
“…In the current era of COVID-19, the whole world is facing hardships in satisfying clients' needs regarding providing merchandise administration, manufacturing, and other daily needs things. This global emergency has constrained manufacturers, organizations, and specialist co-ops to reconsider the current creation strategy, conveying administrations to clients, client interaction, inventory network organization, circular economy, integration of items, green transition, and digitalization [8][9]. However, throughout the history of industrial unrest history, it has been seen that enterprises have the caliber and demonstrated their capability to the remarkable transformation.…”
Section: Goals Of Industry 60mentioning
confidence: 99%
“…However, throughout the history of industrial unrest history, it has been seen that enterprises have the caliber and demonstrated their capability to the remarkable transformation. In addition, endeavors will always be ready to accept this transformation toward the weather change impartiality and change in digital governance in an adaptable and foreseeable world [10][11][12].…”
Section: Goals Of Industry 60mentioning
confidence: 99%